Building a global teledermatology collaboration. (12th February 2016) - Bobbs, Melanie; Bayer, Michelle; Frazer, Tifany; Humphrey, Stephen; Wilson, Barbara; Olasz, Edit; Holland, Kristen; Kuzminski, Jacquelyn
Abstract: Skin disease is common in low‐resource countries and is associated with significant morbidity. The disease burden is often heightened by lack of access to adequate diagnosis and treatment. Teledermatology is a growing healthcare delivery modality that allows access to subspecialty care at a distance. This article describes how a low‐cost teledermatology program was launched through collaboration between the Medical College of Wisconsin and Hillside Healthcare International. Several factors are required for a teledermatology program to be successful, beginning with a partnership between two entities that targets a locally identified need and is mutually beneficial to invested partners. The program should utilize the expertise of each partner, be based on an agreed upon process with clearly defined objectives, and protect patient privacy. After a program is implemented, adaptation to address challenges and best meet the needs of all parties involved will allow for continued success and sustainability. This process can serve as a model for other programs desiring to establish similar teledermatology partnerships in an academic setting.